2020
DOI: 10.1109/mmm.2020.2971375
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Microwave Near-Field Imaging: Prototypes, Systems, and Applications

Abstract: Microwave imaging is a science which evolves from detecting techniques to evaluate hidden or embedded objects in a structure or media using electromagnetic (EM) waves in the microwave range (i.e., from 300 MHz to 300 GHz). Microwave imaging is often associated with radar detection such as target detection and tracking, weather pattern recognition, and underground surveillance which are far-field applications. In recent years, due to microwave's characteristic that allows penetration into optically opaque media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 129 publications
0
41
0
Order By: Relevance
“…Microwave technology offers a low-cost, mobile, and non-ionizing diagnostic alternative modality for applications such as cerebrovascular disease monitoring or tumor detection. Several studies have shown that, in the microwave frequency range, a significant difference in dielectric properties exists between normal and pathological tissues [ 1 , 2 , 3 , 4 ]. Consequently, several research teams are working on this topic around the world and some imaging systems dedicated to these applications are emerging [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microwave technology offers a low-cost, mobile, and non-ionizing diagnostic alternative modality for applications such as cerebrovascular disease monitoring or tumor detection. Several studies have shown that, in the microwave frequency range, a significant difference in dielectric properties exists between normal and pathological tissues [ 1 , 2 , 3 , 4 ]. Consequently, several research teams are working on this topic around the world and some imaging systems dedicated to these applications are emerging [ 5 , 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial contrast in dielectric properties has been established between normal and malignant breast tissue over a broad frequency range from 0.5 to 50 GHz [14]. Based on this dielectric contrast, several microwave imaging systems [15] and algorithms [16] for breast cancer detection have been developed which resulted in multiple clinical prototypes [17].…”
Section: Introductionmentioning
confidence: 99%
“…Within the last 20 years, microwave imaging has attracted significant interest in medical applications, and a number of research groups around the world are now working on developing efficient microwave imaging systems. [1][2][3] In general, a microwave imaging system is comprised of hardware and software components. The hardware collects microwave scattering data from the object under test.…”
Section: Introductionmentioning
confidence: 99%